Porositas Serbuk Jahe Merah (Zingiber officinale Roscae var. Rubrum) terhadap Variasi Suhu dan Kadar Gula Pasir - Sinabutar, Kristin Valentina; Sari, Dessy Agustina (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Ginger is one of Indonesia's most abundant and widespread cultivated plants and is widely used in people's daily lives as a raw material and additive in the manufacture of food and beverages. One type of ginger that is in great demand in the herbal beverage industry is red ginger. The bioactive compounds found in ginger include 6-gingerol, 6-paradol, 6-methylshogaol, 8-methylshogaol, 8-gingerol, 10-gingerol and 6-shogaol. Red ginger contains various bioactive compounds with pharmacological effects such as analgesic, anti-inflammatory, anti-cancer, antioxidant and cardiotonic effects. Scanning Electron Microscopy (SEM) is a microscopy technique used to produce high-resolution images of the surface of an electron sample. This study aimed to analyze the porosity of red ginger powder against variations in temperature and sugar content. The temperatures were 80 and 90°C with a sugar content of 60 and 100%. The results showed that the increase and decrease in the percentage of porosity values were caused by differences in temperature variations applied to the crystallization process. The rate of red ginger powder's porosity that approaches the fresh red ginger rate is red ginger powder at 80°C and 60% crystallization agent. The research results contributed to the characteristics of the materials used and the development of red ginger drink powder products.